MEASURES FOR STRENGTHENING OF INFORMATION SPACE IN LATGALE AND SECURING OF THE LATGALIAN LANGUAGE IN ELECTRONIC MEDIA - Mjartāns, Dainis (Via Latgalica, 2017)
The existence of two separate and distinctly different information spaces is acutely apparent in Latgale, and this situation is heightened by easily picked up Russian and Belarussian television programming as well as illegal satellite operator (smartcard) sharing. Considering these circumstances – and the fact that residents are exposed to vastly different information and interpretations about national, international, economic, social and cultural developments – national Latvian media policy is focused on forging closer links in the realm of information between Latgale and other regions of Latvia, thereby guaranteeing that residents of the border areas are informed of national processes and developments in international events. What steps should be taken in order to, with a reasonable amount of investment, reach as large an audience as possible and promote the development of diverse content for the Latgalian audience? The author of the article analyses the goals and support measures initiated by the Latgale electronic media programme of the National Electronic Mass Media Council (NEPLP) for Latgalian electronic media and producer groups. The programme is a set of measures and activities based on the public service remit for public and commercial media, which includes technical solutions for improving broadcasting standards. In particular, the programme focuses on supporting content generation at local radio stations, which in Latgale continue to be an important source of information and have substantial audiences. The article focuses on tasks that should be performed by the Latgale multimedia studio of Latvian Radio. The studio is a precondition for increasing the public media audience in Latgale as well as for the consolidation of Latgalian identity and protection of the Latgalian language. Based on the communicative needs of Latgalian speakers, the author accents the need for electronic media in the Latgalian language. In-depth studies regarding the demand for and use of written materials in the Latgalian language would help in developing a strategy for the coming years for shaping policy in regard to the preservation and further development of the Latgalian language.